2001
DOI: 10.1046/j.1440-1746.2001.02408.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of hiatus hernia and gastric mucosal atrophy in the development of reflux esophagitis in the elderly

Abstract: Aging, male gender, HH and closed-type GMA are most likely the risk factors of endoscopically proven reflux esophagitis in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
89
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 26 publications
14
89
1
Order By: Relevance
“…We are unable to explain the discrepancy in the chronological changes in the diaphragmatic hiatus and BMI observed in our female subjects, and further studies are needed to clarify the factors involved. Aging may have some role in increasing the size of the diaphragmatic hiatus in our study subjects, since an age-related increase in the incidence of hiatal hernia has been previously demonstrated in women (2,3).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We are unable to explain the discrepancy in the chronological changes in the diaphragmatic hiatus and BMI observed in our female subjects, and further studies are needed to clarify the factors involved. Aging may have some role in increasing the size of the diaphragmatic hiatus in our study subjects, since an age-related increase in the incidence of hiatal hernia has been previously demonstrated in women (2,3).…”
Section: Discussionmentioning
confidence: 85%
“…GERD is influenced by multiple factors, including gastric acid secretion, hiatal hernia, the lower esophageal sphincter function, esophageal motility, esophageal perception and others (1,(3)(4)(5)28). The prevalence of GERD has increased among Asian populations in recent decades, and the increment in the rate of GERD in Asians is thought to be caused by several factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis and classification of reflux esophagitis were based on the Los Angeles classification [8] . Barrett's esophagus was diagnosed when columnar epithelium was seen to extend the Z line and confirmed histologically that showed specialized intestinal metaplasia.…”
Section: Upper Gastrointestinal Endoscopymentioning
confidence: 99%
“…Although many investigators have reported the prevalence of erosive esophagitis [8] , the prevalence of NERD has not been investigated in China. Our study was designed to analyze the spectrum of GERD subjects based on presenting symptoms and endoscopic findings.…”
Section: Introductionmentioning
confidence: 99%